Public and patient involvement in the development of an internet‐based guide for persistent somatic symptoms (GUIDE.PSS): A qualitative study on the needs of those affected - Eirin Fränkl; Nele Hasenbank; Karin Dumröse; Bernd Löwe; Sebastian Kohlmann (Health Expectations)
Abstract Background Persistent somatic symptoms (PSS) frequently remain under‐treated in health care settings. Evidence‐based services that lead affected individuals to early guideline‐based care are currently missing. This study aimed to identify the needs of those affected concerning an internet‐based guide. The second aim was to evaluate public and patient involvement (PPI). Methods Participants experiencing PSS for at least 6 months were recruited via hospitals, psychotherapeutic practices and self‐help organizations. Qualitative data were gathered via ideation discussions and prioritization tasks. Thematic analysis was conducted to gain insight on the needs of people with lived experiences. PPI was quantitatively evaluated with the Public and Patient Engagement Evaluation Tool. Results A total of 12 individuals participated (eight females, ages 22–66 years, duration of symptoms 1–43 years). Participants wanted to feel more supported, validated, in control and engaged with managing their health. Content‐related preferences included education, self‐help, social support and contact addresses. The majority of participants (>90%) experienced their involvement as worthwhile. Conclusions To the best of our knowledge, this is one of the first studies describing PPI in intervention development for PSS. The involvement was perceived as a valuable contribution to the development process. Patient or Public Contribution Adults with lived experiences were involved at the level of collaboration through the establishment of a participatory research team (PRT) and at the level of consultation through a workshop series, including one of the coauthors. They were involved in developing and validating intervention material and checking data interpretation.